Circulation and suspended sediment dynamics in a tropical estuary under different morphological setting - PAIVA,BÁRBARA P. (2016)
ABSTRACT Estuarine processes are directly related to the interaction of its forcing conditions with the local morphology. In this study we assess the implications of the opening of a new inlet on the hydrodynamics and suspended sediment concentration (SSC). A set of physical parameters have been measured in the Itanhém river estuary, a small, shallow and mangrove fringed tropical estuary in Northeastern Brazil. Field surveys have been conducted in August 2007 and January 2008, separated by an important morphological change. Our observations show that even shortening the lower estuary channel in 2 km, the inlet opening did not imply in changes in the estuarine circulation. However, SSC increased after the inlet opening. General estuarine circulation showed synodical modulation of tidal asymmetry and residual suspended sediment transport. The estuary showed flood dominance at spring tide and ebb dominance at neap tide. Although not directly changing the estuarine hydrodynamics, the morphological change resulted in an important increase in SSC. This increase might be related to a facilitated import of inner shelf sediment through a shorter channel, having important implications for the estuarine sedimentation processes.